PELAKSANAAN PEMBELAJARAN SENI BUDAYA MENGGUNAKAN METODE SELF DIRECTED LEARNING DI SMA N 2 RANAH BATAHAN - Widia , Elsa; Fitri, Hasminda; Hadi, Harisnal (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This study aims to identify and describe the implementation of cultural arts learning using the self-directed learning method at SMAN 2 Ranah Batahan. The type of research used is qualitative research with a descriptive approach. The research instrument is the researcher themselves, assisted by supporting instruments such as stationery and a mobile phone. Data collection techniques include observation, interviews, literature study, and documentation. The data analysis techniques in this study include data reduction, data presentation, and drawing conclusions. The research results and discussion conclude that the learning process has proven to be effective. The implementation of cultural arts learning on traditional dance material using the self-directed learning method in Class XI.1 SMAN 2 Ranah Batahan was carried out through four meetings. Students were able to go through the learning stages starting from understanding the concept of traditional dance, discussing and arranging choreography in groups, to performing the dance in the field. Thus, traditional dance learning based on self-directed learning can be said to be effective in achieving learning objectives while also supporting the achievement of the independent curriculum.